PENANDA FUNGSI GRAMATIKAL BAHASA KOREA - , ANDRI SAEFUDIN ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Korean language is a language of Altay family (Sohn, 1999:11). Generally, languages of Altay family have a structure of clause S-O-V, but in Korean language, subject sometimes can appear behind of object. According to Hong (2002:21) markers of grammatical function of Korean language have been highly developed into various forms, functions, and uses. Thesemarkers are word classes which have a very important role in the formation of clause. Therefore, understanding of markers is very important for early Korean language learner in Indonesia. The aim of this research is to describe the form, function, placement, and importance of using subject, object, complement, and adverb makers of Korean language. This research is syncrony, data was collected from grammar books of Korean language which are in written and recorded forms. Then data was analyzed by translational, referential, and distributional methods. The techniques of distributional method which used are immediate constituent analysis, substitution, omission, and addition. The results obtained from the data analysis showed that Korean language has three forms of Ps (-i, -ga, dan âkkeseo), three forms of Po (-reul, -eul, dan â l),four forms of Ppel (-i, -ga, -wa, dan âkwa), and nineteen forms of Pkt (-e, -ege, -hante, -kke, -eseo, -egeseo, -kke, -hanteseo, -ro, -euro, -roseo, -euroseo, -rosseo, - eurosseo, -cheoreom, -boda, -wa, -kwa, dan hago).All forms of these markersare placed behind the constituents of clause and also mark them as a subject, object, complement, and adverb. Markers-kkeseo, -ege, hante, -kke, egeseo, -kke, and - hanteseoalways follow animate nouns and used only in spoken language. In spoken language, Ps, Po, and Ppel can be omitted while most of Pkets canât be omittedexcept particle -e , -ro, and âeuro. They can be omitted in certain contexts. Key words : marker, Korean language, subject, object, complement, adverb, meaning, form, function, use